Earthquake Hazard Mapping Based on Earthquake Intensity Model in North Maluku Islands - Ningrum, Rohima Wahyu; Achmad, Rahim; Aswan, Marwis; Raharjo, Wiji (TECHNO: JURNAL PENELITIAN, 2024)
Earthquake hazard mapping in the North Maluku region is urgent and essential because this area has a very high earthquake hazard potential. The high level of earthquake vulnerability in the North Maluku region makes it very important to focus mitigation activities to reduce the impact of earthquakes that occur. Earthquake hazard mapping that illustrates the effects of earthquakes on an area is one of the disaster mitigation efforts. In this study, earthquake intensity using the Probability Seismic Hazard Analysis (PSHA) method will be used to analyse the level of earthquake hazard in the North Maluku region. The results of the distribution of Peak Ground Acceleration (PGA) values for North Maluku range from 0.67 - 3.75 g. At the same time, the value of the MMI earthquake intensity scale is in the range of IX-XII. The most incredible earthquake intensity is in the Morotai, West Halmahera, Ternate, Tidore, Bacan, and Obi Island areas. The results of this study can have implications as a reference in safer spatial and infrastructure planning, the preparation of more effective mitigation strategies, and can be a medium for educating the public to be more prepared and responsive to earthquake risks.